Istirâtîjiyyah Ta’lim al-Lughah al-‘Arabiyyah ‘ala Asâsi Khasâ’is al-?alabah - Andi Arif Pamessangi (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2021)
Abstract This research examines the application of Arabic learning strategies that are in accordance with the characteristics of students in the Arabic language education study program, Palopo State Islamic Institute. The purpose of this study was to determine the application of Arabic learning strategies in the Arabic language department of Palopo State Islamic Institute, as well as the lecturers' attention to the characteristics of students in implementing Arabic learning strategies in the Arabic language department of Palopo State Islamic Institute. The method used in this research is qualitative research methods. The data collection instruments in this study were observation, interviews, and questionnaires. The results of this study indicate that lecturers in implementing learning strategies in the Arabic language education study program at the Palopo State Islamic Institute pay attention to student characteristics. The Arabic learning strategies applied are very varied, such as the implementation of strategies in learning using audiovisual media using several strategies that are in accordance with the characteristics and abilities of students. Keywords: application, Arabic learning strategies, characteristics of students Abstrak Penelitian ini mengkaji penerapan strategi pembelajaran bahasa Arab yang sesuai dengan karakteristik peserta didik pada program studi Pendidikan Bahasa Arab Institut Agama Islam Negeri Palopo. Tujuan penelitian ini adalah untuk mengetahui penerapan strategi pembelajaran bahasa Arab di Program Studi Pendidikan Bahasa Arab Institut Agama Islam Negeri Palopo, serta perhatian dosen terhadap karakteristik mahasiswa dalam menerapkan strategi pembelajaran bahasa Arab di Program Studi Pendidikan Bahasa Arab Institut Agama Islam Negeri Palopo. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif. Instrumen pengumpulan data dalam penelitian ini adalah observasi, wawancara, dan angket. Hasil penelitian ini menunjukkan bahwa dosen dalam menerapkan dan memilih strategi pembelajaran pada program studi Pendidikan Bahasa Arab Institut Agama Islam Negeri Palopo sangat memperhatikan karakteristik dan latar belakang mahasiswa. Strategi pembelajaran bahasa Arab yang diterapkan sangat bervariasi, seperti penerapan strategi dalam pembelajaran dengan menggunakan media audiovisual dengan menggunakan beberapa strategi yang sesuai dengan karakteristik dan kemampuan mahasiswa. Kata Kunci: Penerapan, strategi pembelajaran bahasa Arab, karakteristik siswa.